2022
DOI: 10.3389/fphar.2022.576458
|View full text |Cite
|
Sign up to set email alerts
|

Metformin With or Without Clomiphene Citrate Versus Laparoscopic Ovarian Drilling With or Without Clomiphene Citrate to Treat Patients With Clomiphene Citrate-Resistant Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: Introduction: Which is optimal to treat clomiphene citrate-resistant polycystic ovary syndrome (CCR-PCOS) with LOD or metformin remains a problem. There are three inconsistent or even contradictory views.Objectives: The present meta-analysis aimed to evaluate the effectiveness and safety of Metformin with or without CC and to compare them with LOD with or without CC (Met/Met-CC vs. LOD/LOD-CC) in women with CCR-PCOS who also have anovulation.Data source: The PubMed, Cochrane, and Embase databases were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Nearly 5 to 15% of women of reproductive age have PCOS, including ovulation disorder, hyperandrogenism and infertility. 10,11 of insulin resistance is central and mainly based on daily routine, eating modifications and insulin-sensitising agents like metformin, as shown in studies of glucose intolerance and type -2 diabetes. 12,13 In the present study, subfertile PCOS women treated with metformin were more likely to ovulate than those treated with Myo-inositol (p-0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 5 to 15% of women of reproductive age have PCOS, including ovulation disorder, hyperandrogenism and infertility. 10,11 of insulin resistance is central and mainly based on daily routine, eating modifications and insulin-sensitising agents like metformin, as shown in studies of glucose intolerance and type -2 diabetes. 12,13 In the present study, subfertile PCOS women treated with metformin were more likely to ovulate than those treated with Myo-inositol (p-0.001).…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] Alternative, non-pharmacological treatment options such as ultrasound-guided follicular puncture and laparoscopic ovarian drilling also entail certain risks and may lead to postoperative complications like periovarian adhesions and ovarian hypoplasia. [14] While assisted reproductive technologies are already in clinical use, such as intrauterine insemination and in vitro maturation culture of immature eggs are available, their efficacy remains a matter of debate; and often lead to high ovulation rate, low pregnancy rate, high miscarriage rate. [11,15] In addition, ovulation induction and in vitro fertilization may increase economic burden on patients, as well as adverse effects on their psychological status.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The incidence and prevalence of type 2 diabetes mellitus are high, particularly in developing countries such as China, 3 therefore the development of generic metformin hydrochloride (MH) tablets is urgently needed to fill the market gap created by the high demand for original metformin sustained-release tablets for patients with type 2 diabetes. 4,5 Recently, a growing number of studies have suggested benefits of the off-label use of metformin in different conditions, 6 such as the promotion of successful pregnancy in patients with polycystic ovarian syndrome with infertility due to anovulation, 7 weight loss, [8][9][10] cardiovascular protection, 11,12 breast and colorectal cancer, 13,14 glioblastoma, 15,16 amelioration of inflammation, 17,18 as a potential geroprotective agent for dementia, 19,20 and stimulation of hair growth. 21,22 These additional benefits of the off-label use of metformin exacerbate the mismatch between the supply and demand for the original drug.…”
mentioning
confidence: 99%